Police and Criminal Evidence Act 1984 Code H : revised code of practice in connection with : the detention, treatment and questioning by police officers of persons in police detention under section 41 of, and schedule 8 to, the Terrorism Act 2000 : the treatment and questioning by police officers of detained persons in respect of whom an authorisation to question after charge has been given under section 22 of the Counter-Terrorism Act 2008.: revised code of practice in connection with : the detention, treatment and questioning by police officers of persons in police detention under section 41 of, and schedule 8 to, the Terrorism Act 2000 : the treatment and questioning by police officers of detained persons in respect of whom an authorisation to question after charge has been given under section 22 of the Counter-Terrorism Act 2008. (November 2016) - Great Britain., Home Office,
No abstract available